EXPLORING JEPARA WOODCARVING ART AS AN ALTERNATIVE FOR CULTURE-BASED MATHEMATICS LEARNING - Utami, Rahmi Nur Fitria; Muhtadi, Dedi; Solihah, Silvi (Ethnomath Association in cooperation with Universitas Negeri Yogyakarta, 2024)
Culturally-based mathematics learning becomes an important alternative to overcome students' learning difficulties. One relevant cultural product is Jepara Carving Art, which contains geometric concepts as part of ethnomathematics. This study aims to describe the mathematical concepts embedded in Jepara carving art and implement them as an alternative culturally-based mathematics learning method. Using a qualitative approach, data were collected through interviews, observations, and field notes, with the research subjects being Jepara carving artisans. The results show that the mathematical concepts integrated into Jepara carving art include points, lines, angles, slopes (gradients), plane geometry, circles, solid geometry, congruence, and geometric transformations such as reflection and rotation. Additionally, the ethnomathematics of Jepara carving art can be implemented as an alternative culturally-based mathematics learning method, where several ethnomathematical activities relate to school mathematics materials. These findings emphasize the importance of linking local culture with mathematics learning to enhance students' understanding. Therefore, this study recommends the inclusion of Jepara carving art in the curriculum as an effective strategy for culturally-based mathematics learning.